MIMICRY AND HYBRIDITY IN THE FILM THE GREAT GATSBY: A POSTCOLONIAL STUDY - Aris Munandar; Winda Eka Pahla Ayuningtyas; Abi Ihsanullah (Universitas Aki, 2022)
Colonization is a process of the colonizer who dominates the colonized people. The colonizer applies their rules to the colonized people. Colonized people unconsciously act these rules, copying the culture of colonizer people who were considered superior, showing their inferiority feelings to their original culture which is considered inferior, or even copying the colonizer's way of life. Imitating is a way to escape their repressed situation. The objectives of this research are: 1) to describe the scene of cultural identities of mimicry portrayed by Jay Gatsby in the film The Great Gatsby using Homi K. Bhabha's perspective, and 2) to explore the scene of cultural identities of hybridity portrayed by Jay Gatsby. This paper can be categorized into library research and applies the descriptive qualitative method. The data were obtained through words, phrases, and sentences of events contained in The Great Gatsby Movie. The findings are: first, Jay Gatsby mimics the colonial culture and tried to apply it in his life. Second, the personality of Gatsby is a blend: a mixture of two different cultures is said to be a hybrid, and his personality is dominated by an eternal struggle.